Homicide and Mental Disorders—Perpetrators’ Prior Contacts With Psychiatric Services - Selin, Klara Hradilova (Journal of contemporary criminal justice, 2024)
This study examines diagnosed mental health disorders among nearly 800 perpetrators of homicide in Sweden between 2005 and 2017. The analysis is based on information from in- and outpatient registers, which has been linked to crime data on homicide. The results show that four out of the 10 homicide perpetrators had been in contact with psychiatric services during the year prior to the crime. It is about seven times more common for a perpetrator of homicide, irrespective of sex, to have been in contact with psychiatric services during the year prior to the crime than it is for someone in the general population to have such contacts in the course of a calendar year. The prevalence of different psychiatric disorders among homicide perpetrators follows the same pattern as that observed in the general population although at higher levels. In both populations, substance abuse, depression, and anxiety disorders dominate. However, the overrepresentation of substance abuse—especially multi-substance abuse—and personality disorders is particularly high among the perpetrators. Perpetrators of family-related homicide had particularly frequent contacts with psychiatric services prior to the crime. Female perpetrators had been treated for psychiatric disorders more often than men, which may reflect not only actual differences in levels of psychiatric ill-health but also differences in the propensity to seek treatment.